Prevention of Child Marriage, Legal Policy, and Community Da'wah: Reconstruction of Indonesian Marriage Law Through Islamic Sociological Jurisprudence - Achmad Rifai Nur Ashrori; Ahmad Fadlan Adlani; Haikal Akbar; Rizqi Candra Pradana; Andi Muhammad Fahri Akbar (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2026)
Child marriage is still a serious problem in Indonesia that has an impact on social, health, educational, and economic aspects. Although the government has set a minimum age limit for marriage through the revision of the Marriage Law, the practice of child marriage still occurs due to cultural, economic, and religious factors that are less comprehensive. This study aims to analyze efforts to prevent child marriage through legal policies and community da'wah approaches in the perspective of Islamic Sociological Jurisprudence. The research method used is qualitative with a normative-sociological approach. The results of the study show that the effectiveness of the law does not only depend on formal regulations, but also on the internalization of values through da'wah and the role of the community. Therefore, the reconstruction of marriage law in Indonesia needs to integrate legal, social, and religious approaches in order to be able to significantly reduce the number of child marriages.